2015
DOI: 10.1007/s12328-015-0582-y
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal tumor-like lesion originating from colon tuberculosis: a case report and review of the literature

Abstract: A 76-year-old male had a solitary submucosal tumor-like lesion in the sigmoid colon originating from tuberculosis. The lesion, up to 1 cm in diameter, was found incidentally during a routine colonoscopy, which revealed a protuberant submucosal growth with a shallow depression of the overlying mucosa in the center of the tumor. Histologically, the endoscopic biopsy revealed caseating granulomas and infiltration of Langhans giant cells and epithelioid cells, consistent with tuberculosis, were also observed. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Diagnosis of colonic TB can be done by colonoscopy combined with histopathologic and bacteriologic examination. Findings on colonoscopy can range from non-specific ulcerations, nodular lesions, strictures, and, less commonly, polyps [4,7,8,14,15]. These nondescript endoscopic findings make colonic TB easily mistaken with other colonic pathologies such as Crohn's disease and malignancy leading to significant delays in the diagnosis and management as well as unnecessary surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of colonic TB can be done by colonoscopy combined with histopathologic and bacteriologic examination. Findings on colonoscopy can range from non-specific ulcerations, nodular lesions, strictures, and, less commonly, polyps [4,7,8,14,15]. These nondescript endoscopic findings make colonic TB easily mistaken with other colonic pathologies such as Crohn's disease and malignancy leading to significant delays in the diagnosis and management as well as unnecessary surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…These nondescript endoscopic findings make colonic TB easily mistaken with other colonic pathologies such as Crohn's disease and malignancy leading to significant delays in the diagnosis and management as well as unnecessary surgical interventions. The histopathologic examination usually reveals caseating epithelioid granulomas which are very specific for TB [7,8,14]. One retrospective study of 50 patients with colonic TB from India reported that granulomas were seen only in 18% of cases, and caseation was not detected in any case.…”
Section: Discussionmentioning
confidence: 99%